2010
DOI: 10.5488/cmp.13.43001
|View full text |Cite
|
Sign up to set email alerts
|

Quasiaverages, symmetry breaking and irreducible Green functions method

Abstract: The development and applications of the method of quasiaverages to quantum statistical physics and to quantum solid state theory and, in particular, to quantum theory of magnetism, were considered. It was shown that the role of symmetry (and the breaking of symmetries) in combination with the degeneracy of the system was reanalyzed and essentially clarified within the framework of the method of quasiaverages. The problem of finding the ferromagnetic, antiferromagnetic and superconducting "symmetry broken" solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…When working with infinite hierarchies of equations for Green functions 4,5 the main problem is finding the methods for their efficient decoupling, with the aim of obtaining a closed system of equations, which determine the Green functions. In the papers 32,78,79,80,81 devoted to studies of lattice systems of interacting fermions it was shown that for a wide range of problems in statistical mechanics 82,83,84,85 and theory of condensed matter one can outline a fairly systematic recipe for constructing approximate solutions in the framework of irreducible Green functions method. Within this approach one can look from a unified point of view at the main problems of fundamental characters arising in the method of two-time temperature Green functions.…”
Section: The Methods Of Irreducible Green Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…When working with infinite hierarchies of equations for Green functions 4,5 the main problem is finding the methods for their efficient decoupling, with the aim of obtaining a closed system of equations, which determine the Green functions. In the papers 32,78,79,80,81 devoted to studies of lattice systems of interacting fermions it was shown that for a wide range of problems in statistical mechanics 82,83,84,85 and theory of condensed matter one can outline a fairly systematic recipe for constructing approximate solutions in the framework of irreducible Green functions method. Within this approach one can look from a unified point of view at the main problems of fundamental characters arising in the method of two-time temperature Green functions.…”
Section: The Methods Of Irreducible Green Functionsmentioning
confidence: 99%
“…The important point about equations ( 82), (83) is that any approximate solution of SIAM should be consistent with it. Let us remind how to get solution (82). It follows from the system of equations for small-V limit:…”
Section: Quasiparticle Dynamics Of Siammentioning
confidence: 99%
See 1 more Smart Citation
“…One should note that the BCS-Bogoliubov superconductivity theory [1,3,5,10,15] is formulated in terms of a trial (approximating) Hamiltonian H mod , which is a quadratic form with respect to the second-quantized creation and annihilation operators, including the terms responsible for anomalous (or non-diagonal) averages. For the single-band Hubbard model the BCS-Bogoliubov functional of generalized mean fields can be written in the following form [92,93,94,95]…”
Section: The Mean Field Conceptmentioning
confidence: 99%
“…We believe that all these concepts will serve for the future development of physics [17] as useful practical tools. Additional material and discussion of these problems can be found in recent publications [18,19].…”
mentioning
confidence: 99%